Anti-osteoporotic drug use and quality of life in persons with osteoporosis – The Tromsø Study - Fouad, Mahmood (UiT Norges arktiske universitet, 2017)
Introduction: Osteoporosis is characterized by decreased bone mineral density (BMD) and is a risk factor for hip, wrist, and vertebral fractures. Fragility fractures lead to increased mortality, morbidity, pain, immobility, social isolation and depression, which all may affect the quality of life (QoL). Use of anti-osteoporotic drugs (AOD) reduces the risk of fractures and may influence QoL. Objective: To investigate a potential association between AOD use and QoL among women and men with osteoporosis. Methods: This is a cross-sectional study of The Tromsø Study (Tromsø 6). The 12984 study participants were inhabitants in Tromsø aged ≥ 50 years who had osteoporosis, defined by T-score for BMD <-2.5 or from -2.5 to -1.6 combined with prior fracture (n=544). In multivariable linear regression analysis, QoL scores (EQ-5D 3L) was the dependent variable, AOD was independent variable, and adjusted for the covariates age, sex, height, weight, education prior fracture and other diseases. Results: The mean QoL score was 0.68 (SD=0.28) in 54 participants using AOD and 0.82 (SD=0.18) in 424 participants not using AOD. The QoL was inversely associated with use of AOD (B=-0.116, p=0.002) after adjusting for covariates. Conclusion: Persons with osteoporosis who were using AOD had significantly lower QoL compared to the AOD non-users. Confounding by severity or awareness of disease could be a problem, as not all participants knew they had osteoporosis.